Pengembangan Bahan Ajar Matematika Untuk Mendukung Pembelajaran Berdiferensiasi Di Sekolah Dasar - Hayati, Neng Aat; Alamsyah, Trian Pamungkas; Pamungkas, Aan Subhan (Journal Mathematics Education Sigma [JMES], 2024)
The aim of this research is to describe the development of mathematics teaching materials in the form of block and cube learning modules that support differentiated learning. Apart from that, to describe the suitability of teaching materials and students' responses to teaching materials. This type of research uses research and development (RD) with the five steps of the ADDIE development model (analysis, design, development, implementation and evaluation) used in development research. The final product is a learning module in the form of blocks and cubes which is used as a tool in differentiated learning. Expert validation assessment shows the feasibility of teaching material products. The assessment includes: a) validation from two media experts who obtained a score percentage of 85% with the interpretation